2021
DOI: 10.1038/s41598-021-85092-x
|View full text |Cite
|
Sign up to set email alerts
|

Age-dependent and region-specific alteration of parvalbumin neurons, perineuronal nets and microglia in the mouse prefrontal cortex and hippocampus following obesogenic diet consumption

Abstract: Emergent evidence demonstrates that excessive consumption of high fat and high sugar (HFHS) diets has negative consequences on hippocampal and prefrontal cortex (PFC) function. Moreover, the delayed maturation of the PFC including the late development of parvalbumin-expressing (PV) interneurons and perineuronal nets (PNNs) may promote vulnerability to HFHS diet-induced nutritional stress. However, the young brain may have some resistance to diet-induced neuroinflammation. Thus, we examined the impact of a HFHS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 96 publications
3
16
0
Order By: Relevance
“…As expected, we observed a significant age-dependent decrease in neurogenesis and a corresponding agedependent increase in PNNs in CA1 (Fig. 4c,d) 41 . These results provide further supporting evidence that the levels of adult neurogenesis in the dentate gyrus impact CA1 PNN expression.…”
Section: Adult Neurogenesis Modulates Perineuronal Net Expression In Ca1supporting
confidence: 88%
“…As expected, we observed a significant age-dependent decrease in neurogenesis and a corresponding agedependent increase in PNNs in CA1 (Fig. 4c,d) 41 . These results provide further supporting evidence that the levels of adult neurogenesis in the dentate gyrus impact CA1 PNN expression.…”
Section: Adult Neurogenesis Modulates Perineuronal Net Expression In Ca1supporting
confidence: 88%
“…The loss of protective PNNs leaves PV + and other enwrapped neurons susceptible to injury [92,156,157], and accordingly, we found that PNN reductions preceded decreases in PV + neurons in AD [90], where PV + cells are particularly relevant to disease [197][198][199][200]. Indeed, PNN loss is associated with neuronal death and/or degeneration in a number of disease contexts [160,169,176,180,190,193,201]. It should be noted that several studies failed to detect differences in PNN abundance in clinical AD [202][203][204][205], and this may be partly attributable to the brain region under investigation or the method of PNN labeling used.…”
Section: Perineuronal Netsmentioning
confidence: 57%
“…PNN deficits/decreases have also been observed across more diverse diseases, many if not all of which are also generally associated with microglial activation, including multiple sclerosis [169], stroke [180][181][182][183][184], traumatic brain injury [185,186], spinal cord injury [187], epilepsy [188,189], obesogenic high fat and high sugar diet consumption [190], glioma [160], Alzheimer's disease [90,[191][192][193], and schizophrenia [167,[194][195][196]. The loss of protective PNNs leaves PV + and other enwrapped neurons susceptible to injury [92,156,157], and accordingly, we found that PNN reductions preceded decreases in PV + neurons in AD [90], where PV + cells are particularly relevant to disease [197][198][199][200].…”
Section: Perineuronal Netsmentioning
confidence: 99%
“…Exercise also alters PNNs, and the effects are dependent on the brain region examined (Smith et al, 2015 ; Briones et al, 2021 ). Several studies have shown that environmental enrichment either during early life (Carstens et al, 2016 ; Stamenkovic et al, 2017 ; O’Connor et al, 2019 ) or adulthood (Foscarin et al, 2011 ; Slaker et al, 2016 ) alters PNNs, as does a high-fat diet during adolescence (Reichelt et al, 2019 , 2021 ) and adulthood (Dingess et al, 2018 , 2020 ). Two studies have shown circadian/diurnal changes, with higher numbers or intensity of PNNs in the dark phase in rodents (Pantazopoulos et al, 2020 ; Harkness et al, 2021 ).…”
Section: Impact Of Physiological Stimuli On Pnnsmentioning
confidence: 99%